How to exploit BIM/IFC for 3D registration of ownership rights in multi-storey buildings: an evidence from Turkey. Issue 27 (13th December 2022) - Guler, Dogus; van Oosterom, Peter; Yomralioglu, Tahsin
Abstract: The condominium rights, which is a special ownership type that can only exist in the buildings that have an occupancy permit, are needed to be examined and depicted as three-dimensional (3D) in order to prevent misinterpretations and disputes regarding Rights, Restrictions, and Responsibilities (RRRs). This paper, therefore, aims to provide the model that extends the Industry Foundation Classes (IFC) schema by referencing Land Administration Domain Model (LADM) in the sense of reusing the Building Information Modeling (BIM)/IFC model of the building for 3D registration of condominium rights in Turkey. The results of the study show that there is a solid potential to benefit from BIM/IFC model in order for both 3D representation of the ownership rights in the multi-storey buildings and obtaining the semantics of the condominiums in terms of wide ranges of attributes such as area, volume, land share, and RRRs.